Application of Stem Cell Therapy for ACL Graft Regeneration. (2nd August 2021) - Wang, Canlong; Hu, Yejun; Zhang, Shichen; Ruan, Dengfeng; Huang, Zizhan; He, Peiwen; Cai, Honglu; Heng, Boon Chin; Chen, Xiao; Shen, Weiliang
Abstract : Graft regeneration after anterior cruciate ligament (ACL) reconstruction surgery is a complex three-stage process, which usually takes a long duration and often results in fibrous scar tissue formation that exerts a detrimental impact on the patients' prognosis. Hence, as a regeneration technique, stem cell transplantation has attracted increasing attention. Several different stem cell types have been utilized in animal experiments, and almost all of these have shown good capacity in improving tendon-bone regeneration. Various differentiation inducers have been widely applied together with stem cells to enhance specific lineage differentiation, such as recombinant gene transfection, growth factors, and biomaterials. Among the various different types of stem cells, bone marrow-derived mesenchymal stem cells (BMSCs) have been investigated the most, while ligament stem progenitor cells (LDSCs) have demonstrated the best potential in generating tendon/ligament lineage cells. In the clinic, 4 relevant completed trials have been reported, but only one trial with BMSCs showed improved outcomes, while 5 relevant trials are still in progress. This review describes the process of ACL graft regeneration after implantation and summarizes the current application of stem cells from bench to bedside, as well as discusses future perspectives in this field.